Less Operating and More Overtriage: National Trends in Interfacility Transfer of Facial Fracture Patients. Issue 5 (14th March 2022) - Wasicek, Philip J.; Kantar, Rami S.; Gebran, Selim; Yoon, Joshua; Kalsi, Richa; Morrison, Jonathan J.; Nam, Arthur J.
Abstract : Background: The purpose of this study was to characterize demographics, injury patterns, and initial management trends of facial fracture patients who were subject to interfacility transfer. Methods: Using the National Trauma Data Bank from 2007 to 2015, facial fracture patients arriving by interfacility transfer were included in the study. Results: Over 9 years, 171, 618 patients were included, with 37.5 percent having an isolated facial injury. Isolated facial injury patients tended to be younger, less frequently white, more frequently assaulted, and more frequently underwent facial fracture operative repair during the index admission (all, p < 0.001). From 2007 to 2015, insurance coverage increased from 54.6 to 79.0 percent ( R 2 = 0.90, p < 0.001). In addition, there was a 45 percent proportional increase in patients 50 to 89 years of age compared to a 20 percent decrease in patients 0 to 39 years of age (both, R 2 = 0.99, p < 0.001). The proportion of transfer patients with isolated facial injury increased over the study period (32.0 to 39.4 percent, R 2 = 0.90, p < 0.001); however, there was a decline in operative intervention (29.5 to 22.1 percent, R 2 = 0.94, p < 0.001) and a 151 percent increase in the proportion discharged from the emergency department upon transfer arrival ( R 2 = 0.99, p < 0.001). Conclusions: Facial fracture patients subject to interfacility transfer comprise a wide array of demographics and injury patterns, with most having concomitant injuries and only a minority undergoing immediate operative intervention. Over time, this demographic has become older, sustained more isolated facial injury, and undergone fewer immediate operative interventions and is more frequently insured and more frequently discharged from the emergency department upon transfer arrival, reflecting increasing rates of secondary overtriage.